Gene transfer into corn earworm (Helicoverpa zea) embryos. - DeVault, J D; Hughes, K J; Leopold, R A; Johnson, O A; Narang, S K (Genome Research, 1996)
Transposable elements with short inverted repeats at their termini have been identified in a number of diverse insect species and have proven to be useful gene delivery vectors for the transformation of Drosophila melanogaster. In this report we examine the ability of the D. melanogaster hobo element to transpose in lepidopteran species. A Trichoplusia ni (cabbage looper) and a Helicoverpa zea (corn earworm) embryonic cell line were found to be capable of supporting productive transposition of the hobo element as measured by a plasmid-based excision assay. Furthermore, hobo transposition was detected in H. zea embryos in a manner consistent with that seen for the cell line. In both cases, transposition/excision was found to be independent of vector-encoded transposase functions, indicating that endogenous genes are involved in hobo mobility. Finally, we demonstrate the stable insertion of the bacterial lacZ gene into the H. zea genome. These data demonstrate that hobo elements are capable of transgressing species boundaries and functioning in non-drosophilid cellular environments. More importantly, this represents the first description of a genetic transformation system for a lepidopteran species.
10.1101/gr.6.7.571